A systematic review of inequalities in psychosocial outcomes for women with breast cancer according to residential location and Indigenous status in Australia. Issue 10 (14th March 2016) - Youl, PH; Dasgupta, P; Youlden, D; Aitken, JF; Garvey, G; Zorbas, H; Chynoweth, J; Wallington, I; Baade, PD
Abstract: Background: The aim of this systematic review was to examine variations in psychosocial outcomes by residential location and Indigenous status in women diagnosed with breast cancer (BC) in Australia. Methods: Systematic searches were undertaken using multiple databases covering articles between 1 January 1990 and 1 March 2015 focusing on adult women with BC in an Australian setting and measuring quality of life (QOL), psychological distress or psychosocial support. Results: Thirteen quantitative and three qualitative articles were included. Two quantitative and one qualitative article were rated high quality, seven moderate and the remaining were low quality. No studies examining inequalities by Indigenous status were identified. Non‐metropolitan women were more likely to record lower QOL relating to breast cancer‐specific concerns and reported a lack of information and resources specific to their needs. Continuity of support, ongoing care and access to specialist and allied health professionals were major concerns for non‐metropolitan women. Non‐metropolitan women identified unmet needs in relation to travel, fear of cancer recurrence and lack of psychosocial support. Conclusions: Overall, there was a lack of evidence relating to variations in psychosocial outcomes for women with BC according to residential status or Indigenous status. While the review identified some specific concerns for non‐metropolitan women with BC, it was limited by the lack of good quality studies using standardised measures. Copyright © 2016 John Wiley & Sons, Ltd.